A sustainable supply chain finance ecosystem: a review and conceptual framework - Liao, Ziling; Prataviera, Lorenzo Bruno; Ghadge, Abhijeet; Abushaikha, Ismail (Elsevier, 2025)
Supply chain finance (SCF) is a set of instruments for optimizing working capital and improving supply chain efficiency. The evolving field of sustainable supply chain finance (SSCF) extends SCF with a growing focus on sustainability. While existing research has primarily focused on the economic benefits of SCF, its potential to generate broader sustainability benefits across environmental, social, and governance dimensions has received limited attention. Moreover, discussions on SSCF solutions and stakeholder interactions remain insufficient, necessitating further exploration to consolidate current research. This study seeks to explore the role of sustainability in SCF and proposes an SSCF ecosystem. A systematic literature review (SLR) of SCF and sustainability resulted in the analysis of 70 interdisciplinary journal papers published between 2008 and 2023. The SSCF ecosystem is defined as a collaborative network of stakeholders leveraging financial tools and sustainability metrics to create shared value and sustainability goals across the supply chain. By applying stakeholder theory and CIMO logic, the study develops a conceptual framework to explain how SSCF mechanisms and interventions produce desirable outcomes for stakeholders. Key influencing factors were identified across four sustainability dimensions—economic, environmental, social, and governance—along with core stakeholders, including buyers, financial institutions, and suppliers, supported by technology/logistics providers and ESG information providers. The study contributes by linking stakeholders to two distinct categories of SSCF solutions: buyer-centric accounts payable financing and supplier-centric accounts receivable financing. Lastly, it proposes future research directions by examining SSCF as an independent subject and capturing its links to traditional SCF.
Keywords: 3509 Transportation, Logistics and Supply Chains; 35 Commerce, Management, Tourism and Services; 3507 Strategy, Management and Organisational Behaviour; 12 Responsible Consumption and Production; Operations Research; Sustainable supply chain finance; Supply chain finance; Sustainability; Supply chain performance